Pengaruh Metode Pengeringan dan Penambahan Ekstrak Daun Binahong Terhadap Karakteristik Biskuit - Muhamad Pahmi Pradana; Mohammad Prasanto Bimantio; Reni Astuti Widyowanti (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Binahong leaves are still widely used only as medicine, not yet able to reach a wider user profile. Research was conducted on the effect of drying methods and the addition of binahong leaf extract on the characteristics of biscuits. The purpose of this study was to determine the effect of three drying method variations and the addition of binahong leaf extract on biscuit characteristics, as well as to identify the drying method and concentration of binahong leaf extract that provide the highest antioxidant activity. The research design used was a Randomized Block Design (RBD) with two factors, namely drying method variations with three levels: direct sunlight, oven drying at 60°C, and indirect sunlight; and the addition of binahong leaf extract with three levels: 1%, 5%, and 10% of flour weight. The analyses carried out included physical properties (total color difference) and chemical properties (moisture content, ash content, fat content, protein content, carbohydrate by difference, and antioxidant activity). The results showed that both drying method and binahong leaf extract addition significantly affected the characteristics of biscuits. The best treatment was obtained in A2B3 (oven drying method with 10% binahong leaf extract addition), which produced the highest antioxidant activity of 60.33%. Further research is recommended on thickening or powdering the extract to reduce moisture content as low as possible so that the biscuits can meet the SNI biscuit standard 2973:2022, with a maximum moisture content of 5%.